IS THE MARKET OVERT RULE APPLICABLE UNDER THE OHADA UNIFORM ACT RELATING TO GENERAL COMMERCIAL LAW IN CAMEROON? - Egute, Matthew (IJRDO - Journal of Social Science and Humanities Research, 2021)
The “market overt” has been established in this paper as an open market, legally constituted and runs between the hours of sunrise and sunset within the village and town markets in Cameroon. Generally, the law insists that only a true owner of goods can sell and transfer good title (property in the goods) in the goods sold within the market. This is legally described by the common law maxim of “Nemo dat quod non habet” (No one can give what he does not have or possess). If we were to end here then commerce and commercial transactions may be very difficult and may even come to a halt. In a bid to overcome the difficulties, the English common law developed some exceptions to the general rule, which exceptions include, “sale in market overt” and the rule later became a statutory principle under the English Sale of Goods Act, 1893 (as amended). This implies that, a bona fide purchaser for value that buys in an open market without knowledge of the seller’s defective title could acquire good title in the goods sold or purchased. Cameroon by virtue of her colonial heritage, inherited the common law principles from Great Britain, alongside civil law principles from France respectively. By this venture, the “market overt rule” became a principle of law in English Cameroon, while the English Sale of Goods Act, 1983 served as a Statute of General Application. The Sale of Goods Act was later replaced in Cameroon by the OHADA Uniform Act Relating to General Commercial Law, even though the courts of the two English speaking Regions still apply the provisions of the English Sale of Goods Act, where the OHADA Uniform Act is silent. The burning question which this paper attempted to address was whether the OHADA Uniform Act, which replaced the 1893 Act, has provided for the “market overt rule”, in a bid to secure and guarantee smooth trade and commerce? Expressly, the Uniform Act does not. But when Article 205 was impliedly interpreted, we came to the conclusion that the “market overt rule” is guaranteed and covered considering the fact that Article 205 stipulates for commercial sale of goods, subject to the observation and preservation of common law rules, the market overt itself being a common law principle. This implies that, the OHADA Uniform Act through Article 205 indirectly recognizes common law rules – the “market overt rule” inclusive. We then concluded and suggested that despite the acceptance and the application of the market overt rule in Cameroon, it transactions should not be extended to cover the transfer of title in stolen goods and the Uniform Act should be amended and more provisions should be added to protect a bona fide purchase who buys from a non-owner in an open recognized market, as well as the rightful owner whose goods were stolen.